Incidence of Polytrauma in the Casualty Emergency Department of a Tertiary Care Hospital in Dhaka City (Journal of Current and Advance Medical Research, 2024)
Background: Polytrauma is a public health problem in every country.Objective: The purpose of the present study was to assess the incidence of Polytrauma in the Casualty Emergency Department of a tertiary care hospital in Dhaka city.Methodology: This cross-sectional study was carried out in the casualty of Emergency Department of Dhaka Medical College Hospital, Dhaka, Bangladesh. The patients who were admitted from January 2014 to December 2014 were included in this study. This study includes all the patients with polytrauma, most of whom underwent laparotomy or other types of surgery like suprapubic cystostomy, amputation, surgical toileting, chest drainage, but a small number was managed with non-operative approach. Immediately after admission, the patients were subjected to resuscitation, primary survey and history taking including pre-hospital retrieval. A tabulated sheet of questionnaire was given to all the patients and answer was taken by conversation and examination.Results: A total number of 100 patients were recruited for this study. The mean age with SD of the study population was 33.5±12.5 with the range of 3 to 67 years. The male female ratio is 7.33:1. The victims of polytrauma sustained their injury from different kinds of trauma. Out of hundred cases with polytrauma, road traffic accidents was the most common cause which included motor vehicle accident, pedestrian and motor cycle accident and resulted in a total of 63 casualty occupying 63% of the entire series. Polytrauma resulted fall from height occurred in 10 (10%) cases. Stab injury caused polytrauma in 5 (5%) cases.Conclusion: In conclusion majority of the study population is young adult with the predominance of male presented with road traffic accident.Journal of Current and Advance Medical Research, July 2023;10(2):60-64